Fostering Learning Motivation for Citizens to Learn Functional Literacy at PKBM Wisata, Pahandut Seberang Village Palangka Raya City - Susan Daniel; Pintarsama Telaumbanua (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to describe: 1) the implementation of functional literacy learning, 2) the tutor's efforts in fostering learning motivation. This research is descriptive research with a qualitative approach. The research subjects are the owner of the institution, tutors and residents learning functional literacy of PKBM Wisata, Pahandut Seberang Village, Palangka Raya City. Methods of collecting data with interviews, and documentation. The data analysis technique used was data reduction, data display and conclusion drawing. Triangulation is done to explain the validity of the data by using the source. The results showed that: (1) The implementation of functional literacy learning learning was carried out, firstly verifying prospective tutors and prospective students, then tutors and organizers identifying needs according to the competence of participants, both tutors compiling syllabus and lesson plans, third tutors prepare the necessary teaching materials and modules. (2) Efforts are made to grow the motivation of learning residents by providing direction to learning residents and providing training that can support them to become entrepreneurs. In addition, tutors and institutions always motivate learning residents by providing transportation money, gifts, and always emphasizing on every citizen learns to be even more active in the learning process carried out by the institution.